Frontispiece: Scaling Up DNA Origami Lattice Assembly. Issue 33 (18th June 2021) - Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Castro, Mario; Linko, Veikko; Keller, Adrian
Abstract : Surface‐assisted hierarchical DNA origami assembly can be scaled up to produce highly homogeneous polycrystalline DNA origami lattices at the mica‐electrolyte interface over cm 2 areas with only minor boundary effects at the substrate edges. At total DNA costs of € 0.12 per cm 2, this large‐scale DNA origami nanopatterning technique holds great promise for the development and fabrication of versatile functional surfaces. For more details see the Full Paper by A. Keller, V. Linko et al. on page 8564 ff.